A Comparative Study Using Two Types of Photobioreactor for Cultivation of Chlorella vulgaris Microalgae - Noor Aziah Serri; Nur Hazwani Halmi; Mohd Asyraf Kassim; Mohd Salman Abu Mansor (Engineering Proceedings, 2025)
Effective vessel design is crucial for the viability and practicality of microalgae cultivation, aiming for high biomass production. This study tested two different 5-litre vessel designs for cultivating Chlorella vulgaris, aiming to produce a high biomass and evaluate lipid production. The study varied pH medium (6.5–10.5), light intensity (200–1000 lux), and CO2 concentrations (5–15%) to assess each reactor’s performance. The aerated vessel (tubular shape) produced 21.05% lipid concentration, while the fabricated vessel (oval shape) produced 20.14% at optimum conditions. The aerated vessel performed best at pH 10.5, 5% CO2, and 1000 lux light intensity, whereas the fabricated vessel’s optimum conditions were pH 10.5, 15% CO2, and a white LED system. The highest biomass was 0.432 g/L in aerated tubular vessels and 0.281 g/L in fabricated oval-shaped vessels. Both systems performed well and are suitable for further study with other microalgae types.